Cascadable current-mode multifunction filter with two inputs and three outputs using CDTAs - Dumawipata, Teerasilapa; Tangsrirat, Worapong; Surakampontorn, Wanlop (My University, 2007)
The current-controlled current-mode universal filter with two inputs and three outputs using current differencing transconductance amplifiers (CDTAs) as active components is presented. The proposed circuit configuration consisting of only three CDTAs and two grounded capacitors exhibits low-input and high-output impedances, which is advantageous from an integration point of view and is important for easy cascading in the current-mode operations. By properly connecting the input and output terminals, the filter can simultaneously realize all the standard filter functions, namely lowpass (LP), bandpass (BP), highpass (HP), bandstop (BS) and allpass (AP), without any component matching conditions. The natural angular frequency (ωo) and the bandwidth (ωo/Q) of the proposed filters can be electronically controlled, thanks to the tunability properties of the CDTAs. All the passive and active sensitivities are low. SPICE simulation results are included to confirm the theory. ©2007 IEEE.
Keywords: Current differencing transconductance amplifier (CDTA); Multifunction filter